Aggrecan and Hyaluronan: The Infamous Cartilage Polyelectrolytes – Then and Now - Plaas, Anna H. K.; Moran, Meghan M.; Sandy, John D.; Hascall, Vincent C. (Springer International Publishing, 2023)
Cartilagescartilage are unique in the family of connective tissuesTissue in that they contain a high concentration of the glycosaminoglycansGlycosaminoglycan, chondroitinChondroitin sulfateSulfate and keratanKeratan sulfate attached to the core protein of the proteoglycanProteoglycan, aggrecanAggrecan. Multiple aggrecan molecules are organized in the extracellular matrixMatrixExtracellular matrix via a domain-specific molecular interaction with hyaluronan and a link protein, and these high molecular weight aggregates are immobilized within the collagenCollagen and glycoproteinGlycoprotein networkNetwork. The high negative charge densityDensity of glycosaminoglycans provides hydrophilicity, high osmotic swelling pressurePressure and conformational flexibility, which together function to absorb fluctuations in biomechanical stressesStress on cartilage during movementMovement of an articular jointJoint. We have summarized information on the history and current knowledge obtained by biochemical and genetic approaches, on cell-mediated regulationRegulation of aggrecan metabolismMetabolism and its role in skeletalSkeletal development, growth as well as during the development of joint diseaseDisease. In addition, we describe the pathways for hyaluronanHyaluronan metabolism, with particular focus on the role as a “metabolicMetabolic rheostatRheostat” during chondrocyte responses in cartilage remodelingRemodeling in growth and disease.